Seaweed Biomaterials - Maiti, Sabyasachi (IntechOpen, 2018)
Seaweeds are the rich sources of naturally occurring valuable therapeutic substances. Many different marine organisms have been explored for novel bioactive compounds that exhibit antiviral, antitumor, anticoagulant, antidiabetic, antimicrobial, and antiinflammatory activities. Nonetheless, seaweed-derived polysaccharides have also been studied for the design of different kinds of novel drug delivery systems. Over the last 30-40 years, research has been ongoing in the search for novel seaweed-derived bioactive compounds. This book covers up-to-date information on seaweed biomaterials and their therapeutic potentials.